Analisis Aplikasi Ensiklopedia Hadis 9 Imam Versi Android sebagai Sarana Dakwah di Media Sosial - Pikri Hafidz Maulid (Jurnal Penelitian Ilmu Ushuluddin, 2022)
This study aims to analyze the Android version of the 9 Imam Hadith Encyclopedia application as a means of da'wah on social media. This research is a descriptive model using the literature review method, namely by analyzing various sources analytically so that the resulting data is accurate and reliable. The results and discussion of this study include the profile of the 9 imam hadith encyclopedia application, the relevance of the 9 imam hadith encyclopedia application with da'wah, and analysis of the android version of the 9 imam encyclopedia application as a means of da'wah on social media. The answer to the question of the analysis article on the Android version of the 9 Imam Hadith Encyclopedia Application concludes that the hadith application is currently widely distributed in the community, but those that reach the realm of da'wah require an application that is accountable both in terms of content and application and the 9 Imam Hadith Encyclopedia has all the accountability criteria because it has Imam Hadith. Besides being equipped with features that make it easy to learn hadith, this application is also growing, including the latest content for da'wah needs, namely Selected Hadith, Hadith Posters, Hadith Podcasts, Hadith Playlists, Greeting Cards, Arbain Hadith and many more. With this application, grounding the hadith on social media is not a difficult thing anymore, so it is highly recommended to support the community's da'wah needs on social media.